Applications of Agent-Based Modelling Techniques to Studies of Historical Epidemics: The 1918 Flu in Newfoundland and Labrador - Dimka, Jessica; Orbann, Carolyn; Sattenspiel, Lisa (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
The purpose of this article is twofold. First, the study addresses questions related to the spread and impact of the 1918 influenza pandemic in a small Newfoundland community, focusing on the role of large social institutions including an orphanage, school, and churches. Records indicate, for example, that residents of the orphanage in St. Anthony, our study community, experienced an increased risk of infection at different times during the epidemic than did members of the general community. Further, archival sources show that a variety of public health measures including closure of public gathering spaces were implemented throughout Newfoundland, but evidence suggests that the success of these measures varied. Second, this paper presents an argument for the important role computer simulation models can play in historical research, which is demonstrated using results from simulations focusing on social, demographic, and cultural factors, including behaviours and interactions of community residents. These examples highlight how modelling techniques can be used in historical research to address gaps in archival sources and help direct future research paths, and to test counterfactual scenarios to identify important factors influencing observed outcomes.